Conceptualization of the Bangsa in Indonesian national song texts: A cognitive linguistic study - Andono, Afid (Privietlab, 2025)
This study aims to reveal the forms of conceptual metaphors in the lyrics of Indonesian national songs and explain how these forms represent national ideology and shape collective identity. Using the Cognitive Linguistics approach through conceptual metaphor theory (Lakoff & Johnson, 1980), five national songs were analyzed: Indonesia Raya, Ibu Pertiwi, Bangun Pemudi Pemuda, Hari Merdeka, and Garuda Pancasila. The data were collected through the listening method and note-taking technique and then analyzed using source-target domain mapping technique and image schema. The results show that there are 17 metaphorical data divided into five main patterns: +BODY is BODY+, +HOMELAND+, +Mother/Living Creature+, +Movement+, and +PERSONAL COMMITMENT+. Each metaphor reflects ideological values such as organic, territorial, affective, progressive, and personal-communal nationalism. This finding confirms that national songs are linguistic and ideological texts that shape the way people view the concept of Bangsa, both collectively and emotionally.